An in vitro Comparison of Two Replacement Techniques Utilizing Fascia Lata after Cranial Cruciate Ligament Transection in the Dog - Coetzee, G. L. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
The immediate postoperative biomechanical properties of an “underand-over” cranial cruciate ligament (CCL) replacement technique consisting of fascia lata and the lateral onethird of the patellar ligament, were compared with that of a modified intra- and extracapsular “under-and-over-the-top” (UOTT) method. The right CCL in twelve adult dogs was dissected out and replaced with an autograft. The contralateral, intact CCL served as the control. In group A, the graft was secured to the lateral femoral condyle with a spiked washer and screw. In group B the intracapsular graft was secured to the lateral femoro-fabellar ligament, and the remainder to the patellar tendon. Both CCL replacement techniques exhibited a 2.0 ± 0.5 mm anterior drawer immediately after the operation. After skeletonization of the stifles, the length and cross-sectional area of the intact CCL and CCL substitutes were determined. Each bone-ligament unit was tested in linear tension to failure at a fixed distraction rate of 15 mm/s with the stifle in 120° flexion. Data was processed to obtain the corresponding material parameters (modulus, stress and strain in the linear loading region, and energy absorption to maximum load).The immediate postoperative structural and material properties of the “under-and-over” cranial cruciate ligament replacement technique with autogenous fascia lata, were compared to that of a modified intra- and extracapsular “under-and-over-the-top” (UOTT) method. The combined UOT T technique was slightly stronger (6%), but allowed 2.8 ± 0.9 mm more cranial tibial displacement at maximum linear force.
Keywords: Cranial cruciate ligament; fascia lata; biomechanical properties; dog